Designing the Positive Organizational Behavior Questionnaire: Prevalidation Results - Wladimir A. Stroh; Vasilisa V. Dayneko (Peoples' Friendship University of Russia (RUDN University), 2023)
The purpose of the study was to design an original questionnaire for diagnosing positive organizational behavior (POB) of employees and further test its psychometric indicators of validity and reliability. The author of the concept of POB F. Luthans did not offer any diagnostic tool for assessing it; therefore, the authors decided to create own questionnaire. A theoretical analysis of the concept and existing scales for diagnosing the five components of POB (self-efficacy, hope, optimism, subjective well-being and emotional intelligence) was conducted. The empirical study was in the form of an online survey. The sample consisted of 172 respondents, aged 22 to 60, who worked in various fields of activity. The psychometric indicators of the POB questionnaire were assessed, including the reliability and consistency of the items, the correspondence of the theoretical conceptualization to the factorial structure of the questionnaire. The construct validity of the questionnaire was tested using The Satisfaction With Life Scale by E. Diener et al. (adapted by D. Leontiev and E. Osin) and The Life Orientation Test by M. Scheier et al. (adapted by T. Gordeeva, O. Sychev and E. Osin). As a result of the confirmatory factor analysis, a five-factor structure of the questionnaire was formed, which corresponded to the ideas about the five-component structure of POB in F. Luthans' theoretical concept. The reliability was assessed by analyzing the values of Cronbach's alpha. The results showed sufficient reliability and consistency of the items of the questionnaire (the value of Cronbach's alpha of the total scale of POB was 0.890). The assessment of construct validity confirmed the presence of significant relationships between the individual subscales of the POB questionnaire and the scales of satisfaction with life and life orientation, which indicated the substantive similarity of the scales. The study showed that the created measuring tool had sufficient validity and reliability and could be used for further research purposes.